Upgrading Digital Literacy for Gen Z in Madrasah through Basic Computer Training - Prasojo, Budi; Adianto, Adianto; Sutrisno, Imam; Tanjung, Ihsan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Generation Z learners, born into an era of ubiquitous digital technology, require robust digital-literacy skills to participate effectively in education and society. However, many students in Islamic elementary schools (madrasah ibtidaiyah) still struggle with basic computer operation, especially when confronted with computer-based testing environments. This study aimed to upgrade the digital literacy of female students at MI Al Fatah II through a structured, hands-on Basic Computer Training (BCT) program. The training emphasized fundamental computer use, file management, text editing, and online-examination simulation. A participatory action-research design was adopted, involving 25 students over three weeks. Quantitative data were collected via pre- and post-tests, and qualitative data through observation and reflective interviews. The average literacy score increased from 48.2 to 86.7, yielding a normalized gain of 0.74 (high effectiveness). Students also exhibited enhanced self-confidence and ethical awareness in digital environments. The findings highlight that gender-responsive, context-based digital-literacy programs can effectively prepare young learners in faith-based schools to engage in online learning ecosystems and align with Indonesia’s Merdeka Belajar policy and the Sustainable Development Goals (SDGs 4 & 9).